2005
DOI: 10.1111/j.1365-2133.2005.07048.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary angio-oedema with normal C1 inhibitor in a family with affected women and men

Abstract: Recurrent angio-oedema is a sign of various acquired and inherited disease entities, including hereditary angio-oedema types I and II that result from a genetic deficiency of C1 inhibitor, and a recently described type of dominantly inherited angio-oedema, which does not show a deficiency of C1 inhibitor. Until now, this new type of hereditary angio-oedema, designated as hereditary angio-oedema type III, has been assumed to be a disorder specific to females. We now describe a four-generation family with domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 17 publications
0
45
1
2
Order By: Relevance
“…It has been reported that angiotensin-converting enzyme inhibitors can induce an exacerbation of symptoms in patients with HAE-C1-INH [16]. We observed a 60-year-old man from a family with HAE with normal C1-INH who has had arterial hypertension since age 30 and had four tongue swellings following treatments with captopril and enalapril [5]. The last episode occurred when the patient received only hydrochlorothiazide and metoprolol.…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 89%
See 2 more Smart Citations
“…It has been reported that angiotensin-converting enzyme inhibitors can induce an exacerbation of symptoms in patients with HAE-C1-INH [16]. We observed a 60-year-old man from a family with HAE with normal C1-INH who has had arterial hypertension since age 30 and had four tongue swellings following treatments with captopril and enalapril [5]. The last episode occurred when the patient received only hydrochlorothiazide and metoprolol.…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 89%
“…In two families, however, the existence of clinically unaffected male carriers has been deduced [2,3]. In 2006, we described a family with dominantly inherited angioedema and normal C1 inhibitor activity in which not only fi ve female but also three male family members were clinically affected [5]. Later, more male patients with HAE III were reported, among them were patients with HAE-FXII [8•,12•].…”
Section: Gendermentioning
confidence: 94%
See 1 more Smart Citation
“…Bazı olgularda menarş öncesinde olup puberte sonrası ve/veya yüksek östrojen düzeyleriyle alevlenen AE tablosu görülürken, bazı olgularda düşük veya normal seviyedeki östrojen düzeylerinde bile AE görülebildiği bildirilmiştir [19][20][21] . Daha sonraları ise akrabalık bağı olan bazı erkek olgularda da görüldüğü saptanmıştır 22,23 . Tip 3 HAE'nın erkeklerden akrabalık bağı bulunan diğer erkek olgulara da geçişinin görülmesi nedeniyle otozomal dominant kalıtımlı olduğu ve penetransının düşük olması nedeniyle toplumdaki asemptomatik taşıyıcı kadınların sayısının az olmadığı düşünülmektedir.…”
Section: Herediter Anjiyoödemunclassified
“…HAE with normal C1INH, formerly known as HAE type III, was initially documented only in women; however, it was later also reported in males [27]. In 2006, it was revealed that some of these families had mutations in the F12 gene encoding Hageman factor [28], and more recently mutations in the gene encoding angiopoietin-1 (ANGPT1) and the gene encoding plasminogen (PLG) have also been documented [29-34].…”
Section: Introductionmentioning
confidence: 99%